2012
DOI: 10.4161/hv.20098
|View full text |Cite
|
Sign up to set email alerts
|

Increase of meningococcal serogroup Y cases in Europe: A reason for concern?

Abstract: Neisseria meningitidis is differentiated into 12 distinct serogroups of which A, B, C, W-135, X and Y are medically most important and represent a major health problem in one or more parts of the world. The epidemiology of N. meningitidis is unpredictable over time and across geographic regions. A sudden increase or decrease of IMD or meningococcal carriage may occur anywhere at any time. Recent epidemiological surveillance indicates an increase of serogroup Y IMD in some parts of Europe and data from various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In recently published data for 2010 and 2011, the highest relative proportion for serogroup Y IMD has been reported from Scandinavian countries (up to 55%), followed by the most central/Western European countries (5-10%), while the relative proportion has been lowest (<5%) in most of the Eastern/South-Eastern European countries. 1,2 For 2012, this picture has not significantly changed. In Figure 1, the absolute number and relative proportion of serogroup Y cases in 2012 are presented for 33 European countries from data that was available.…”
Section: Resultsmentioning
confidence: 98%
“…In recently published data for 2010 and 2011, the highest relative proportion for serogroup Y IMD has been reported from Scandinavian countries (up to 55%), followed by the most central/Western European countries (5-10%), while the relative proportion has been lowest (<5%) in most of the Eastern/South-Eastern European countries. 1,2 For 2012, this picture has not significantly changed. In Figure 1, the absolute number and relative proportion of serogroup Y cases in 2012 are presented for 33 European countries from data that was available.…”
Section: Resultsmentioning
confidence: 98%
“…16 Recently, an increase in both absolute numbers and relative proportion of serogroup Y cases has been reported in various European countries for 2010. 1 At the moment, it is difficult to predict whether this rising trend in serogroup Y IMD will continue or if it represents only a short-term rise that will be followed by a reduction in disease rates to the previous relatively low levels. The longevity of the epidemics can vary by the serogroup.…”
Section: -12mentioning
confidence: 99%
“…In France, the average age of patients with MenY changed from 76.1 in 2005 to 20.8 in 2010, which coincided with the overall rise in MenY cases 5. Of particular concern, a study in 2009 by the European Monitoring Group on Meningococci showed that in England and Wales, only 13% of children under the age of 5 had protective antibody titres against MenY 6.…”
Section: Discussionmentioning
confidence: 99%